The Role of Parents in Improving Memorization Al-Qur'an Juz 30 at Hidayatul Elementary School Mubtadiin Montong Tuban - Sukarti, Sukarti; Rofiq, Ainur (Anjasmoro: Islamic Interdisciplinary Journal, 2024)
The role of parents is very important in supporting and improving memorization of the Qur'an, especially Juz 30, at MI Hidayatul Mubtadiin Montong Tuban. Parents have a great influence on children's lives, including in religious education. This study aims to analyze the role of parents in improving children's memorization of the Qur'an, evaluate students' memorization achievements under parental guidance, and identify supporting and inhibiting factors of the role of parents in improving children's memorization of the Qur'an at MI Hidayatul Mubtadiin. This study uses a qualitative method with a descriptive approach. The results of the study indicate that the role of parents is very significant in several aspects, namely as role models, motivators, guides, facilitators, and managers. Parents are role models for children because children's behavior tends to imitate their parents' actions. As motivators, parents provide strong encouragement so that children are more enthusiastic about memorizing the Qur'an. In addition, they also act as guides when children face difficulties, provide adequate facilities for smooth memorization, and manage children's activities so that they remain focused. This study also found that the active role of parents can improve students' Al-Qur'an memorization achievements so the role of parents greatly determines the success of the Tahfidz Juz 30 program at the madrasah. The success factors of the Tahfidz program are divided into two, namely supporting factors and inhibiting factors. Internal supporting factors include motivation given by parents, while external factors are positive school environment and friends. The internal inhibiting factor is student laziness, while the external factor is gadget addiction which has a negative impact on student memorization.